Relação entre as capacidades do pensamento crítico e o desempenho dos estudantes de Química no ENADE - Santana, Edenilza Mendonça (2018)
This study sought to assess the performance of students entering and graduating from graduate courses and Bachelor's degree in chemistry from Brazil, in the national examination performance of students (ENADE) in 2011 and 2014, with a view to identify whether the higher education courses in Chemistry provides students the development of critical thinking skills. The study is based on a documentary research, developed through the mixed method, from the concomitant triangulation strategy, in which the issues were used to General knowledge of the ENADE and micro-data on these issues that are provided by the National Institute of studies and research Anísio Teixeira (INEP). The classification of objective issues of general training of ENADE-2011 and 2014, according to the taxonomy of critical thinking. From this classification, worked with the performance variable, corresponding to the grades obtained by the students on the issues, relating it to three independent variables: i) course (baccalaureate and teaching licensure, whereas students freshmen and seniors); II) institution (public or private) and iii) school (public or private). Employed the Chi-square test for the analysis of these pairs, in order to identify which variable is more relevant to the students ' performance on issues that demand critical thinking capabilities. With the analysis made, it was found that the issues require critical thinking skills to your resolution and in variable course, graduating students of both courses feature superior performance. In the institution, when students are owned by private institutions of higher education, students graduating graduation exhibit superior performance, even when the students are in public institutions, the freshmen have a greater emphasis on performance. In the school, students of public schools demonstrate better performance when they are seniors. Students who come from private schools, have a superior performance when they are entering. With regard to data observed for the year 2011, no statistically significant difference was identified in any of the comparisons made between freshmen and graduates students, independent of the variable used.